LEGAL REGULATION OF RULES OF ETHICAL BEHAVIOR OF POLICE OFFICERS AND THE PLACE OF ADMINISTRATIVE LEGISLATION IN IT (Bulletin of criminological association of Ukraine, 2024)
In the scientific article, a comprehensive review and elaboration of the existing theoretical and scientific achievements regarding the legal regulation of the rules of ethical behavior of police officers and the formulation on this basis of the appropriate classification according to the legal force of normative legal acts were carried out. It has been proven that the legal regulation of the rules of ethical behavior of police officers is a normative influence on the actions and behavior of the subjects of legal relations, with the aim of regulating the rules of behavior of all participants in legal relations. The legal regulation of the rules of ethical behavior of police officers is a series of legal acts that regulate the main law enforcement function in the state and their system of legal relations. According to the legal force of normative legal acts, the legal regulation of the rules of ethical behavior of police officers is: 1. The Constitution of Ukraine; 2. International legal acts; 3. Laws of Ukraine, which contain the main organizational aspects of police activity, the principles of police activity, as well as the main provisions regarding police service, including separate ethical norms; 4. Normative and legal acts of central state bodies (resolutions of the Verkhovna Rada of Ukraine, decrees of the President of Ukraine, resolutions of the Cabinet of Ministers of Ukraine); 5. Departmental normative legal acts (orders, instructions, orders of the Ministry of Internal Affairs of Ukraine and the National Police of Ukraine); 6. Acts of individual action.
Keywords: legal regulation; rules of ethical behavior; professional and ethical requirements; police officer; administrative legislation